A needs assessment study for optimising prescribing practice in secondary care junior doctors: The Antibiotic Prescribing Education among Doctors (APED) - Gharbi,M; Moore,LSP; Castro,Sanchez E; Spanoudakis,E; Grady,C; Holmes,A; Drumright,LN (BMC Infectious Diseases, 2016)
Introduction: Appropriate antimicrobial prescribing is essential for patient care, yet up tohalf of antimicrobial prescriptions written in the UK are sub-optimal. Improvingprescriber education has recently been promoted as a mechanism to optimiseantimicrobial use, but identification of key learning objectives to facilitate this is so farlacking. Using qualitative methods we investigated junior doctor knowledge, attitudes,and behaviours around antimicrobial prescribing to identify key areas to address infuture educational programmes.Methods: A cross-sectional survey of qualified doctors in training in West London wasundertaken exploring antimicrobial prescribing practices and educational needs.Results: Among 140 junior doctors from 5 London hospitals, a third (34%) reportedprescribing primarily unsupervised, and two thirds (67%) reported difficulties obtainingprescribing support outside of hours. 20% stated not feeling confident in writing anantimicrobial prescription, but confidence was increased through having confirmatorydiagnostic results (24%) and obtaining advice from a senior doctor (26%); whether thissenior was from their own specialty, or an infection-specialist, varied significantly(p<0.01) by experience. Only a small percentage (5-13%; depending on number ofyears post-qualification) of participants stated their previous antimicrobial educationwas effective. 60% of those in their first year post qualification reported wanting furthereducation in antimicrobial prescribing, rising to 74% among more experienced juniordoctors. Specific areas of educational need identified were (i) principles of antimicrobialprescribing, (ii) diagnosis of infections, (iii) clinical review of patients with infections, (iv)prescribing in the context of antimicrobial resistance, and (v) laboratory testing and testresults.Discussion: A significant proportion of junior doctors report lone prescribing ofantimicrobials in the context of low self-perceived confidence and knowledge in